Pendidikan Multikultural dan Relevansinya dengan Pendidikan Agama Islam - Hanif Tofiqurrohman (Jurnal Kependidikan, 2019)
Abstract The purpose of writing this article is as a reflection material for the character of Indonesian education in the midst of diversity and cultural diversity. The reality of multi-religious life, language, culture, and ethnicity requires transformation in the field of education. Conventional education patterns that are oriented towards strengthening science should begin to build awareness that teaching diversity to students is important. Multicultural education as a process in shaping the mindset of students in order to have a high social life and mutual respect for each other, in the implementation of multicultural education is very parallel and relevant if collaborated with Islamic religious education values. Keywords multicultural education, relevance, islamic education Abstrak Tujuan Penulisan artikel ini adalah sebagai bahan refleksi bagi karakter pendidikan masyarakat Indonesia di tengah kemajemukan dan keragaman budaya. Realitas kehidupan multiagama, bahasa, kultur, dan etnis membutuhkan transformasi dalam bidang pendidikan. Pola-pola pendidikan konvensional yang berorientasi pada penguatan ilmu pengetahuan seyogyanya mulai terbangun kesadaran bahwa mengajarkan keragaman pada anak didik adalah penting. Pendidikan multikultural sebagai sebuah proses dalam membentuk pola pikir anak didik agar memiliki jiwa sosial yang tinggi dan saling menghormati pada sesamanya, dalam implementasinya pendidikan multikultural sangat sejajar dan relevan jika dikolaborasikan dengan nilai-nilai pendidikan agama Islam. Kata Kunci pendidikan multikultural, relevansi, pendidikan agama islam